The Effect of Enrichment Activities on Positive Thinking and on the Skill of the High-dribble and the Scoring of Stability - Amina Abbas Hassan (Journal of Global Pharma Technology, 2018)
Through the experience of the researcher as a teacher working to develop the thinking of the student and give students freedom to think as well as to encourage them to participate positively in the classroom and learn the basic skills in an interesting and enjoyable so used the activities of enrichment and its connection to the process of positive thinking, and the utility of enrichment activities to transfer students from the status of the recipient Negative to the state of positive interaction during the course of the study and because of the recent enrichment activities and use in other materials such as mathematics, chemistry and Arabic use within the classroom, and the introduction of these activities in the enrichment curriculum. One of the contemporary trends in the development of the curriculum of sports in different stages of education, in order to achieve the principle of sport for all and so the researcher remained only to achieve the objectives of this study, which came as follows - to know the degree of positive thinking among fifth-grade students prepare - the number of educational units enrichment activities to learn to target of stability, and the high level of basketball in the fifth grade preparatory students. The research community was determined by the students of Al-Adhamiya for the fifth grade of Literary Literacy, which were 90 students divided into three groups (A + B + C). The research community was determined by the intentional method. The sample was randomly selected in the drawing method, and the number of (60) students distributed equally to the two divisions. Experimental Division A and Division C were withdrawn and pretest tests were conducted with selected skills and then the proposed curriculum was implemented. With 9 weeks. The number of educational units per week reached two educational units, (18) educational units. Different exercises were adopted, different from basketball activities and skills in warm-up and aim to avoid boredom and introduce the element of suspense and fun in the hearts of students. After completion of the curriculum, the researcher conducted post tests under the same pretest conditions, data and statistical treatment and concluded that the use of enrichment activities in the curriculum for the teaching of physical education for female students has a direct and significant impact on the learning of students, skills in question. Enrichment activities also helped to open the door for dialogue and discussion and to express opinions freely through the division of one class into small groups, which in turn helped to learn the skills studied, and the leadership of each group helped to learn the courage and strengthen the personality of the female student.Keywords: Enrichment activities, Positive thinking, High-dribble and the scoring of stability.